MENINGKATKAN MINAT BELAJAR SISWA DENGAN PAKEM MENGGUNAKAN APLIKASI ENGLISH CHILDREN DALAM PENGENALAN BAHASA INGGRIS - Moh Zainuddin; Mohammad Fatoni (Universitas PGRI Yogyakarta, 2021)
As educators in the era of globalization in welcoming the millennial era, it is very necessary to update learning methods equipped with learning media that are suitable for learning needs, in this case PAKEM learning uses the